PENGARUH PERSONAL SELLING DAN IKLAN TERHADAP PROSES KEPUTUSAN MAHASISWA MEMILIH TEMPAT KULIAH - Ovilia Nasya Yuswanto; Anna Wulandari (Jurnal Pengembangan Wiraswasta, 2019)
This research was conducted to determine the effect of personal selling and advertising on the decision process of students choosing where to study. The sample of this study was 78 students in the Gunung Puteri region, Bogor using the accidental sampling method. This research was conducted by distributing questionnaires to students as respondents. The analysis technique used is multiple linear regression. The study produces a model of multiple linear regression equation Y = 11,068 + 0,101 X1 + 0,607 X2 which is feasible to explain the effect of personal selling and advertising on the decision of students choosing a college. Personal Selling has no influence on the student's decision to choose where to study. Advertising has an influence on the decision process of students to choose a place of study in a positive direction. Keywords: Personal Selling, Advertising, Decision process. Penelitian ini dilakukan untuk mengetahui pengaruh personal selling dan iklan terhadap proses keputusan mahasiswa memilih tempat kuliah. Sampel penelitian ini adalah 78 mahasiswa di wilayah Gunung Puteri, Bogor dengan metode accidental sampling. Penelitian ini dilakukan dengan cara menyebarkan kuesioner kepada mahasiswa sebagai responden. Teknik analisis yang digunakan adalah regresi linier ganda. Penelitian menghasilkan model persamaan regresi linier ganda Y = 11.068 + 0,101 X1 + 0,607 X2 yang layak untuk menjelaskan pengaruh personal selling dan iklan terhadap keputusan mahasiswa memilih kuliah. Personal Selling tidak memiliki pengaruh terhadap keputusan mahasiswa memilih tempat kuliah. Iklan memiliki pengaruh terhadap proses keputusan mahasiswa memilih tempat kuliah dengan arah positif.Kata kunci:Personal Selling, Iklan, Proses Keputusan